T-SPOT. TB assay and tuberculin skin test for diagnosis and screening of tuberculosis: First report in a Sri lankan population - Ratnatunga, Champa N; Thevanesam, Vasanthi; Madegedara, Dushantha; Dissanayake, Neranjan LA; Kumara, K.G.R Athula (Asian Journal of Medical Sciences, 2015)
Objective: Guidelines encourage evaluation of an Interferon Gamma Release Assay (IGRA) in the local setting, particularly in low/ middle income, Bacillus Calmette Guerin (BCG) vaccinated populations where the assays have shown variable utility. The TSPOT.TB assay and the Tuberculin Skin Test (TST) were compared in diagnosis of active tuberculosis (TB) and in contact screening in an adult Sri Lankan population. Methods: A prospective study including confirmed TB cases (n=75), controls (n-74) and close contacts of smear positive cases (n=27) was carried out at the regional Chest clinic in Kandy district. Clinical history and investigation findings, including TST results were recorded and the TSPOT.TB (Oxford Immunotec) performed. Results: The presence of diabetes and cavitation were significant predictors of TSPOT.TB positivity, while TST had no significant clinical predictors. In the diagnosis of active TB, TSPOT.TB sensitivity was 73.3% (95% CI, 58.6-84.6%) and a specificity was 72% (95% CI, 62.0-85.5%) while the TST sensitivity was 70.7% (95% CI, 54.2-83.3%) and specificity was 64.1% (95% CI, 49.7-76.5%). In contact investigation neither test showed an association with exposure level. Cost estimate was LKR 9400.00 per TSPOT.TB test compared to LKR 200.00 per TST. A high (21%) indeterminate result rate was seen with the TSPOT.TB assay Conclusions: This study did not show any advantage in using TSPOT.TB over TST in this setting. Asian Journal of Medical Sciences Vol.7(1) 2015 14-19